Strengthening the Role of Cadres and Village Midwives to Support the Cervical Cancer Awareness Movement in Puhu Payangan Village, Gianyar, Bali, Indonesia - Desak Putu Oki Lestari; Sri Ratna Dewi; Ni Wayan Armerinayanti (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Cervical cancer is the most common type of cancer in Balinese women, and most of the cervical cancer patients came in advanced condition. The health survey conducted in the village of Puhu, Payangan, Gianyar, found that the coverage of cervical cancer screening is 12%, which is considered as low. Payangan’s sub-district health centers (Puskesmas) have made an effort to give free PAP smear screenings to the local community, but it still has not received a good response. This is related to the community’s lack of knowledge on cervical cancer, low awareness of cancer screening, and false stigma about PAP smear examination. To overcome this problem, an effort is needed to increase awareness about the need for PAP smear screening by shaping it into a cervix cancer awareness movement "Gardavi", involving village midwives and housewife members of Empowerment and Family Welfare Group (PKK) in Puhu Village as cadres. Methods that are used in this community service include training for midwives, activation of tiered information system involving midwives-cadres and the community, knowledge provision as well as motivating cadres. This event is done to increase the role of village midwives and cadres to actively participate in PAP smear screenings in their region, therefore, it may increase screening outcomes and lower mother morbidity and mortality numbers due to cervical cancer. This event results in increased midwives’ knowledge and skill on the technique of sampling PAP smear independently, increased visits to the Community Health Sub-Center (Pustu) for PAP smear examination, creation of a midwives-cadres-community coordination system, cadres independently playing an active role in motivating the village community to do screening, as well as increased cadres’ optimism.